Synthesis and analgesic activity of new pyrazole-containing derivatives of 1,2,4-triazole-3-thiol - S. O. Fedotov; A. S. Hotsulia; Yu. V. Karpenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Pain represents a primary symptom of numerous diseases and conditions, affecting millions of people worldwide. Effective analgesic medications can alleviate or eliminate pain, thereby enhancing patients’ quality of life and assisting them in resuming normal physical and social activities. However, several existing analgesics may carry unwanted side effects, such as ulcers, blood clotting issues, drowsiness, and more. The development of new analgesics is focused on creating drugs that are both effective and associated with fewer adverse effects. Considering the continuous rise in the number of patients dealing with neurological, oncological, and other conditions accompanied by chronic pain, there is a growing demand for innovative methods of treatment and pain management. The combination of two different heterocyclic fragments within one molecule makes it possible to use the possibilities of influencing such a molecule on various mechanisms of occurrence and development of various pathological conditions, including those accompanied by pain. Chemical modifications of pyrazole and 1,2,4-triazole structures, involving their incorporation into a single molecule, have the potential, as suggested by in silico predictions, to yield biologically active compounds with analgesic properties.